Meta Analysis: Analysis of Students' Mathematical Critical Thinking Ability Through the Inquiry Learning Model - Suryonegoro, Bayu Murti; Wardono, Wardono; Asih, Tri Sri Noor; Mariani, Scolastika; Rosyida, Isnaini; Aini, Aulia Hurul (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: The importance of critical mathematical thinking skills in mathematics learning in the current era of the industrial revolution and globalization has encouraged research to evaluate the impact of learning models, one of which is the inquiry model, on students' critical mathematical thinking skills. Methodology: This meta-analysis review was conducted using the stages of data collection, literature review using PRISMA, statistical analysis, qualitative study, and conclusions. Data were collected through national and international journals and proceedings indexed by Sinta or Scopus to make the information obtained more credible. This study uses the PRISMA framework with the steps identification, screening, eligibility, and inclusion to help transparency, consistency, and completeness of reporting the results of the meta-analysis review. Main Findings: Based on the research results, inquiry learning significantly influences students' critical mathematical thinking skills. This is evidenced by increased motivation, curiosity, and student involvement in learning. However, this finding requires follow-up in the future, for example, the development of innovations in textbook learning in the form of textbooks or other learning media. Novelty/Originality of this study: The study analysis of the process of students' critical mathematical thinking skills towards the inquiry learning model in this study was conducted by citing various cross-disciplinary studies and studies from multiple countries or regions to balance more detailed analysis perspectives globally.